Trabalhadores na cidade... caminhos entrecruzados e condições adversas em Marechal Cândido Rondon (1990-2018) - Rodrigues , Daniela Melo (2020)
The current dissertation has as key of access the adverse conditions faced by workers, in order to investigate their presence and ways of living set in Marechal Cândido Rondon – PR, between the years of 1990 and 2018. In this regard, I intend to debate the images produced about these workers and also, starting from them, observing how these aspects permeate their experiences and, mostly, how they highlight their ordinary struggle. The problems facing housing, conviviality networks, values built in the formulated approaches and detachment are part of this debate. The sources used include interviews, articles from the newspaper O Presente, entries from the Reference and Social Assistance Center of Marechal Cândido Rondon – CRAS, etc. This documentation was central to this research. Thus, discussing the to be work demanded to deal with the difficult access to medical and hospital care, the exhausting work relationships, as well as unemployment, problems about how and where to live, among other factors that involve the class condition of these subjects. All of this made up the investigation about the experience of these workers in Western Paraná in latest decades.